1, 2, 3-Benzoxathiazine-2, 2-dioxides – effective inhibitors of human carbonic anhydrases. (1st January 2023) - Ivanova, Jekaterina; Abdoli, Morteza; Nocentini, Alessio; Žalubovskis, Raivis; Supuran, Claudiu T.
Abstract: A series of 1, 2, 3-benzoxathiazine-2, 2-dioxides possessing various substituents in the 5, 7, or 8 position was obtained from corresponding 2-hydroxybenzaldehydes in their reaction with sulfamoyl chloride. 5-, 7-, and 8-aryl substituted 1, 2, 3-benzoxathiazine-2, 2-dioxides were prepared from aryl substituted 2-hydroxybenzaldehydes obtained from 3-, 4-, or 6-bromo-2-hydroxybenzaldehydes via two-step protocol. 1, 2, 3-Benzoxathiazine-2, 2-dioxides were investigated for the inhibition of four human carbonic anhydrase (hCA, EC 4.2.1.1) isoforms, cytosolic hCA I and II and tumour-associated transmembrane hCA IX and XII. Twenty four derivatives of 1, 2, 3-benzoxathiazine 2, 2-dioxide were obtained. Most of them act as nanomolar inhibitors of hCA IX and XII. Almost all compounds except 2d and 5a-e also express nanomolar inhibitory activity for hCA II. hCA I is poorly inhibited or not inhibited by 1, 2, 3-benzoxathiazine 2, 2-dioxides. Some of the new derivatives exhibit promising selectivity towards CA IX/XII over hCA I, although none of the compounds are selective towards CA IX/XII over both hCA I and II.